The Effect of Pursed-Lips Breathing on Children's Respiratory Rate with Pneumonia in Cempaka High Care Unit, Dr. Moewardi Regional Hospital - Nurhidayati, Arini; Rasyida, Zulfa Mahdiatur; Ratrinaningsih, Suciana (Al-Hijrah Indonesia, 2025)
Background: Pneumonia is a lower respiratory tract infection that can be fatal in children, caused by bacteria, viruses, or fungi. Symptoms include fever, cough, and dyspnea. One non-pharmacological therapy to address ineffective breathing patterns is Pursed Lips Breathing (PLB), which can improve alveolar expansion in each lung lobe, normalize respiratory rates, and promote relaxation in children with pneumonia. Objective: This study aimed to determine the effect of PLB on respiratory frequency in childrens with pneumonia at Cempaka High Care Unit, Dr. Moewardi Regional Hospital, Surakarta. Methods: A descriptive case study approach was used, involving two respondents diagnosed with pneumonia. Respiratory rate (RR) was measured before and after PLB intervention, administered twice daily (morning and evening) for three days. Results: Post-intervention, Respondent R’s RR decreased from 44 to 32 breaths/minute, while Respondent S’s RR improved from 32 to 20 breaths/minute. Conclusion: PLB therapy demonstrated changes in respiratory frequency for both respondents. Respondent R’s rate remained indicative of tachypnea, whereas Respondent S achieved a normal range, marked by improved breathing patterns.